(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Glochidion talakonense M. Sankara Rao, J. Swamy, S. Nagaraju, S.B. Padal, M. Tarakeswara Naidu, K. Chandramohan & T. Thulasiah, a new species of Phyllanthaceae from Talakona hills, Seshachalam Biosphere Reserve, Andhra Pradesh, India, is described and illustrated. It is allied to G. karnaticum Chakrab. & M. Gangop., but differs from the latter by stamens, ovary, style and fruit characters. Bangladesh J. Plant Taxon. 23(1): 59-63, 2016 (June)